Making Sense of Modula-2 - Glendinning Irene; Tatham Eric W (International Thomson Business Press, 1994)
This book combines a course in the use of this popular language with an easy-to-follow course on program design based upon current methods. Acknowledgements, Getting Started, Dealing with Data, Structuring Programs, Block Structure and Scope, IF Statement and BOOLEAN Types, FOR Statement and ARRAY Types, WHILE and REPEAT and LOOP Statements, Handling Text Files, CASE Statement and Enumerated Types, RECORD and SET Types, Using Modules, Sorting and Searching Algorithms, A Study in Design, POINTER Types, Binary Trees, Simulation Using a Priority Queue, Low Level Facilities, The Epilogue, Appendices, Index.